Antimicrobial, antioxidant activities, and total phenolic contents of Pycnanthus angolensis Sap and Cryptolepis sanguinolenta root extracts - Francis Adu-Amankwaah; Hephzibah Sam; Chris Yaw Asare; Felix Charles Mills-Robertson (BMC, 2023)
Abstract The death of many people in tropical countries can be attributed to microbial infection, probably, because synthetic antibiotics are failing in the treatment of most microbial infections, attributed to the ability of the microorganisms to mutate and adapt to harsh conditions. This study evaluated, in vitro, the antimicrobial activities, antioxidant potentials, and the total phenolic as well as phytochemical contents of aqueous and ethanol extracts of the root of Cryptolepis sanguinolenta (Lindl.) and the crude sap of Pycnanthus angolensis (Welw) using selected standard bacteria strains (Staphylococcus aureus (ATCC 25,923), Staphylococcus saprophyticus (ATCC 15,305), Escherichia coli (ATCC 25,922), Salmonella typhi (ATCC 19,430), Pseudomonas aeruginosa (ATCC 27,853), and Proteus mirabilis (ATCC 49,565). The modified agar well diffusion method was used to evaluate the antimicrobial activities of the plant extracts. Chloramphenicol and tetracycline were used as positive controls. The extracts were screened for specific phytochemicals with total phenolic contents were determined using Folin Ciocalteu reagent test. The phytoconstituents observed were alkaloids, cardiac glycosides, and saponins in both Cryptolepis sanguinolenta and Pycnanthus angolensis. For the antimicrobial activities, all the test bacteria were susceptible to the crude sap of Pycnanthus angolensis except Proteus mirabilis. In the case of the Cryptolepis sanguinolenta, only S. aureus was susceptible to both aqueous and ethanol extracts. The total phenolic content, expressed in g/100 g GAE, recorded values of 55.427 ± 4.248 for the crude sap of Pycnanthus angolensis, and 11.642 ± 4.248 and 26.888 ± 4.248 for the aqueous and ethanol extracts of Cryptolepis sanguinolenta, respectively. It is concluded that Cryptolepis sanguinolenta and Pycnanthus angolensis are excellent candidates for further development of antimicrobial agents in the fight against microbial infections given the pressing need for novel efficacious agents.